Optimization of biodiesel production from POME using lipase immobilized in PVA-alginate-sulfate beads - Matinja, Idris Adamu (2016)
Palm oil mill effluent (POME) is an agro-industrial wastewater from palm oil processing. It is characterized by presence high organic compounds that cause serious air, soil and water pollutions. Both large and laboratory scale technologies are used to solve the problems that evolved from the discharge of POME. Previously, biodiesel was obtained from POME using immobilized Candida rugosa lipase in Polyvinyl alcohol (PVA) alginate-sulfate beads, which prior that study, was seen as a good substrate for biodiesel production due to its high amount of oil and grease. In this study, biodiesel production from POME using immobilized Candida rugosa lipase in PVA-alginate-sulfate beads was optimized using Box-Behnken design (BBD) of response surface methodology (RSM). Four parameters responsible for biodiesel production from POME were adopted from the previous study; these are methanol/POME ratio, reaction time, weight of the immobilized beads and agitation speed. The highest conversion (91%) and biodiesel yield of oleic methyl esters (65%) and palmitic methyl esters (45%) were obtained at the following optimum conditions; agitation speed (300rpm), POME/methanol ratio (1:6), incubation period (5hours) and weight of the immobilized beads weight (2g). Michaelis-Menten kinetic parameters of the immobilized and free lipase were determined through the hydrolysis of olive oil. Lineweaver-Burk plot indicated the corresponding values of Km and Vmax were 0.0506 g/ml and 21.09 U/ml for free lipase and 0.0686 g/ml and 15.95 U/ml for immobilized lipase. The important fuel properties of the biodiesel such as flash point, kinematic viscosity, water and sediment and copper strip corrosion were evaluated according to the American Society for Testing of Materials (ASTM D6751) and European Standard (EN 14214) and were found to be in good agreement with the standard quality and specification.